The Common Costimulatory and Coinhibitory Signaling Molecules in Head and Neck Squamous Cell Carcinoma - Liao, Peng; Wang, Haofan; Tang, Ya-ling; Tang, Ya-Jie; Liang, Xin-hua (Frontiers in Immunology, 2019)
The development of Head and neck squamous cell carcinoma (HNSCC) is frequently accompanied by complex functional activities of immune cells and the suppression of immune cell function is also getting more and more attention. Normal activation of immune cells requires the coordination of costimulatory and coinhibitory signal molecules. The aberrant competition between these signal molecules directly affect the function of the immune cells and cytokine secretion, finally influence the tumor progression. This review will summarize the features of common costimulatory and coinhibitory molecules, analyze the underlying mechanism of these molecules regulating the malignant progression of HNSCC, and discuss the clinic application of blocking coinhibitory molecules. A deeper understanding of the tumor immune landscape will help insight new concepts to emerge in immune-checkpoint oncology and a new better tumor immunotherapy could be in prospect.